The Role of Social Media in The Formation of Young People's Civic Identity: A Study on University Students in The Reform Era - Yuniarto, Bambang; Khalifatan, Najmi; Adelisah, Adelisah; Qolbi, Rafiqan (Transpublika Publisher, 2025)
This study aims to explore the role of social media in the construction of citizenship identity among students of the Social Studies Study Programme in the reform era. The transformation of information technology, especially the emergence and rapid development of social media, has influenced the way young people voice their identity and understand their position and responsibilities as citizens. This study was conducted using a descriptive qualitative approach, focusing on Tadris Social Studies students at the Cyber State Islamic University Sheikh Nurjati Cirebon. The selection of informants was done purposively, namely those who actively use social media and show concern for social, political and civic issues. Data were collected through in-depth interview techniques and digital observation of students' behaviour and activities on social media platforms. The findings of this study indicate that social media does not solely function as a medium for entertainment and social interaction, but also as a space for learning and reflection that encourages the growth of critical attitudes and awareness of civic values. However, the existence of false information (hoaxes), hate speech and negative content still pose serious challenges that can hinder the process of citizenship identity formation. In this context, strengthening digital literacy is a strategic element that must be considered so that students are able to utilise the media.